VALIDASI MEDIA PEMBELAJARAN VIDEO ANIMASI UNTUK PENINGKATAN KARAKTER NASIONALISME PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Yuyun Puji Utami Ning Muntiani; Novialita Angga Wiratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop and validate an animated video learning medium for Pancasila Education to enhance nationalism charactr. The study addresses the challenge of uninnovativ and unengaging learning media in Pancasila Education, which hinders students' interest and active participation in fostering nationalism. Utilizing a Rsarch and Development (R&D) approach with the ADDIE model, this study specifically focuses on the "Developmnt" and "Evaluation" stages, emphasizing the validity testing of the developed media. Validation was conducted by expert validators, including material, media, and language experts, using product assessment questionnaires. The results show that the animated video learning medium is highly valid, with scores of 84.4% from media experts, 91.1% from language experts, and 100% from material experts. This indicates that the developed animated video learning medium meets high-quality standards in terms of material, media, and language, making it effective for supporting the learning process and fostering nationalism character in students.